Development of QR-Code Assisted Leaflet Media to Improve Junior High School Students' Science Literacy - Widya Puspita Asri (Justek : Jurnal Sains dan Teknologi, 2025)
21st century education requires students to have various basic literacy skills, one of which is science literacy. Science literacy is important in science learning because it can make it more meaningful. Existing facts prove that students' science literacy in Indonesia is still relatively low. It is hoped that the existence of leaflet media assisted by the Quick Response Code (QR-Code) can improve the science literacy skills of junior high school students in learning science. The aim of this research is to describe the level of validity, practicality and effectiveness of QR-Code assisted leaflet media. The method used in this research is development using the ADDIE development stage. The techniques used in data collection are observation, interviews, tests in the form of pretests and posttests, validation sheets, and learning implementation observation sheets. Based on the results of research that has been carried out, leaflet media is declared very valid by experts with a percentage of 90%, practical by observers with a percentage of 90%, and the effectiveness in the n-gain test is 0.71 which is included in the high category. Thus, leaflet media assisted by QR Code is suitable for use in developing science literacy in junior high school students.